Cell wall-anchored nuclease of Streptococcus sanguinis contributes to escape from neutrophil extracellular trap-mediated bacteriocidal activity. - Chisato Morita (Public Library of Science (PLoS), 2014)
Streptococcus sanguinis, a member of the commensal mitis group of streptococci, is a primary colonizer of the tooth surface, and has been implicated in infectious complications including bacteremia and infective endocarditis. During disease progression, S. sanguinis may utilize various cell surface molecules to evade the host immune system to survive in blood. In the present study, we discovered a novel cell surface nuclease with a cell-wall anchor domain, termed SWAN (streptococcal wall-anchored nuclease), and investigated its contribution to bacterial resistance against the bacteriocidal activity of neutrophil extracellular traps (NETs). Recombinant SWAN protein (rSWAN) digested multiple forms of DNA including NET DNA and human RNA, which required both Mg(2+) and Ca(2+) for optimum activity. Furthermore, DNase activity of S. sanguinis was detected around growing colonies on agar plates containing DNA. In-frame deletion of the swan gene mostly reduced that activity. These findings indicated that SWAN is a major nuclease displayed on the surface, which was further confirmed by immuno-detection of SWAN in the cell wall fraction. The sensitivity of S. sanguinis to NET killing was reduced by swan gene deletion. Moreover, heterologous expression of the swan gene rendered a Lactococcus lactis strain more resistant to NET killing. Our results suggest that the SWAN nuclease on the bacterial surface contributes to survival in the potential situation of S. sanguinis encountering NETs during the course of disease progression.